2000
DOI: 10.1080/713671145
|View full text |Cite
|
Sign up to set email alerts
|

Improving Communication with People with an Intellectual Disability: The content validation of the Biala-II profile

Abstract: This study explores the content validity of a pro le used to describe the communication behaviour of people with intellectual disabilities. The pro le, named Biala-II-a Wiradjuri (an Australian Aboriginal language) word for "I understand you"-makes use of the knowledge of informants who are able to provide speci c and detailed information on the ways in which a person communicates. This information can be used by "communication partners" to guide their interactions with a person whom they do not know well. Fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The data indicated that there were major inadequacies in the documentation of the individualised service plans in this sample and it is argued that these de ciencies could prevent service plans from achieving their objective of regulating services and orienting them to the needs and goals of individuals. (p. 73) This focus on meeting the expressed needs of individuals and on improving the ways in which they might exercise more choice and decision-making in their lives was the subject of much of my research in the nineties (Shaddock, Guggenheimer, Rawlings, & Bugel, 1993;Shaddock, Zilber et al, 1993;Zilber, Rawlings, & Shaddock, 1994;Rawlings, Dowse, & Shaddock, 1995;Shaddock, Dowse, Richards, & Spinks, 1998;Shaddock, Spinks, & Esbensen, 2000). In one study we examined the views of people with an intellectual disability about their experiences with individualised plans .…”
mentioning
confidence: 96%
“…The data indicated that there were major inadequacies in the documentation of the individualised service plans in this sample and it is argued that these de ciencies could prevent service plans from achieving their objective of regulating services and orienting them to the needs and goals of individuals. (p. 73) This focus on meeting the expressed needs of individuals and on improving the ways in which they might exercise more choice and decision-making in their lives was the subject of much of my research in the nineties (Shaddock, Guggenheimer, Rawlings, & Bugel, 1993;Shaddock, Zilber et al, 1993;Zilber, Rawlings, & Shaddock, 1994;Rawlings, Dowse, & Shaddock, 1995;Shaddock, Dowse, Richards, & Spinks, 1998;Shaddock, Spinks, & Esbensen, 2000). In one study we examined the views of people with an intellectual disability about their experiences with individualised plans .…”
mentioning
confidence: 96%